Resting heart rate in patients with ischemic heart disease in Saudi Arabia and Egypt - Kinsara, Abdulhalim J (Journal of the Saudi Heart Association, 2011)
AIM: To assess the level of resting heart rate (RHR) in an outpatient population presenting with stable coronary artery disease (CAD) as well as to measure its association with current therapeutic management strategies for cardiovascular events